Financial Report Analysis to Measure Financial Performance at PT. Adaro Energy Indonesia, TBK 2015 – 2021 - Saputra, Raden; Sarumpaet, Hendra Gunawan (Jurnal Multidisiplin Madani, 2023)
Financial Report Analysis is an effort to find out the Performance Results and Health of the Entity, which is an important concern for each entity in making decisions and steps for the next year. The data used in this research is quantitative data and the author uses descriptive methods. The research objective is to look at Financial Performance and Health, using Liquidity Ratios, Solvency Ratios and Profitability Ratios. Information comes from the financial reports of PT Adaro Energy Indonesia, Tbk, for the 2015-2021 period which are listed on the Indonesian Stock Exchange. The research results show that the cash ratio, quick ratio and current ratio are all in good condition, so they are able to pay current debts if needed quickly. Solvency ratios for 2015-2021, from the Debt to Equity Ratio, Long-Term Debt to Equity Ratio and Debt to Asset Ratio, each below 1, indicating that the entity is still able to manage the Entity's Assets and Equity optimally. The 2015-2021 Profitability Ratio, Return on Assets Ratio and Return on Equity Ratio respectively with an average of 6.4% and 10.8% are still low but at the end of 2021 they increased and the Margin Ratio to Gross Profit, to Operational Profit and to Net Profit is still high and it is hoped that in the future the Entity will be able to control Cost of Goods Sold, General Expenses and Other Expenses. Thus, a conclusion can be made that the performance of PT Adaro Energy Tbk is good